PENGEMBANGAN MEDIA KADO TUTU (KARTU DOMINO TUBUH TUMBUHAN) UNTUK PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Ulya Millati, Fiqi; Mushafanah, Qoriati; Reffiane, Fine (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop KADO TUTU (Plant Body Domino Card) media in the science subject of grade IV elementary school that is feasible and practical. The type of research used is Research and Development (R&D) research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. This research was conducted at SDN Bugangan 01. The results of the media expert validation test obtained a percentage of 96%, while the validation of the material expert was 96.6%, where the percentage was included in the